A case report of cardiogenic shock with transcranial color-coded ultrasound monitoring under ECMO - Yuyi Chen; Jingyi Wu; Huiying Chen; Jiefeng Xie; Yuping Liao; Qianwei Zheng; Yu Gan (Frontiers in Cardiovascular Medicine, 2026)
Background Cardiogenic shock (CS) during venoarterial extracorporeal membrane oxygenation (VA-ECMO) support carries high mortality, often due to neurological injury. Precise matching of ECMO flow to cerebral perfusion is critical. Transcranial color-coded sonography (TCCS) offers real-time, non-invasive hemodynamic assessment to guide flow titration, though its clinical integration remains limited. Case presentation This study reports a 58-year-old male firefighter who suffered out-of-hospital cardiac arrest due to acute myocardial infarction, resulting in CS, right frontal lobe hemorrhage, and hypoxic-ischemic encephalopathy. VA-ECMO was initiated on-site and maintained post-resuscitation alongside intra-aortic balloon pump (IABP) and continuous renal replacement therapy (CRRT). TCCS was used throughout hospitalization to monitor middle cerebral artery flow parameters [including pulsatility index (PI), resistivity index (RI), and non-invasive intracranial pressure (nICP)]. These flow indexes were used to guide dynamic ECMO flow adjustments (gradually decreased from 3.25 L/min to 2.12 L/min) to preserve cerebral perfusion within target ranges. At the three-month follow-up, his neurological function recovered, and he was living independently. Six-month follow-up revealed progressive resolution of the intracranial hemorrhage. Conclusion This case demonstrates the feasibility of TCCS-guided neuromonitoring during ECMO support for CS. TCCS provided real-time cerebral hemodynamic data that informed bedside ECMO flow titration. Whether this approach mitigates secondary brain injury or improves neurological outcomes requires further validation.